2023
DOI: 10.1111/ijfs.16655
|View full text |Cite
|
Sign up to set email alerts
|

Identification of β‐casein phenotypes (A1/A2) in the milk of the Indian Jersey crossbreed bovine using the high‐resolution accurate mass spectrometer

Abstract: SummaryFoodomics is an emerging probing method of phenotype investigation of the different milk proteins and their subtypes. The polymorphic nature of the β‐casein (β‐Cn) protein has shown fourteen different protein variants to date in bovines. The analysis of the β‐Cn genetic polymorphism from the milk of the crossbred dairy animals is crucial for the quality assurance of the consumers from the various health concerns, especially those linked with the A1 phenotype which yields β‐casomorphin‐7 on in‐vivo diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In a different study, a specific phenotype of β-casein was determined from 24 different crossbred (A1/A2) Jersey breeds. As a result of this study, which is a proteomic approach, proline and histidine residues were highlighted in the proteome database of A1 and A2 β-casein [10]. Originally, the β-casein protein comprised 209 amino acid chains in the A2 variant.…”
Section: A1 and A2 Milkmentioning
confidence: 99%
See 1 more Smart Citation
“…In a different study, a specific phenotype of β-casein was determined from 24 different crossbred (A1/A2) Jersey breeds. As a result of this study, which is a proteomic approach, proline and histidine residues were highlighted in the proteome database of A1 and A2 β-casein [10]. Originally, the β-casein protein comprised 209 amino acid chains in the A2 variant.…”
Section: A1 and A2 Milkmentioning
confidence: 99%
“…β-casein possesses balanced amino acid nutritional ratio and is useful in maintaining a healthy cycle within the body. β-casein occurs in 13 different variants, with the most commonly known variants being A1 and A2 [8][9][10]. Milk can be classified according to its casein type, primarily due to its various physicochemical properties.…”
Section: Introduction 1cow Milkmentioning
confidence: 99%
“…One significant difference between the A1 and A2 variants of bcasein is the type of digestive products they produce. When the A1 variant is digested through gastrointestinal proteolysis, it creates a bioactive peptide called b-casomorphin-7 (BCM-7), which activates l-opioid receptors of the body (Singh et al, 2023). These International Journal of Food Science and Technology 2024 receptors regulate the body's response to pain.…”
Section: Easy To Digest Chocolatesmentioning
confidence: 99%
“…Singh and his coworkers (2023b) identified β‐casein (β‐Cn) protein genetic polymorphism from the milk of the crossbred dairy animals, especially those linked with the A1 phenotype which yields β‐casomorphin‐7 on in vivo digestion for the quality assurance of the consumers from the various health concerns. They indicated that 17 cows produced A2 β‐Cn (Pro~67) while only 7 yielded the A1 variant (His~67).…”
mentioning
confidence: 99%